Obtenção e caracterização das propriedades fisico-químicas de sais duplos sulfatados para uso em dispositivos ópticos e termoquímicos - OLIVEIRA NETO, João Gomes de (2022)
In recent years, the crystallization of sulfated double salts has gained prominence in the materials science and engineering field. This fact occurs due to the structural, thermal, and optical properties that these systems present, which are inherent to the chemical composition chosen to obtain these materials and which are of great interest to industries that develop optical and thermochemical devices. From this motivation, this work had as main objective the synthesis, characterization and computational studies of sulfated crystals obtained by the solvent slow evaporation method. Among the produced samples, some have an unprecedented character, while others already have structural determination, however, there are no studies on their physicochemical properties reported in literature. The salts synthesized here are part of the Kröhnkite and Tutton salt crystallographic families, in which they exhibit inorganic structures formed from two cations (monovalent and bivalent) that perform chemical bonds in the crystal lattice with water and sulfate molecules. In summary, the structural, morphological, vibrational, thermal, and optical properties were characterized by a range of characterization techniques, such as X-ray diffraction (XRD), scanning and transmission electron microscopy, Fourier transform infrared spectroscopy, Raman spectroscopy, molecular absorption spectroscopy, photoluminescence spectroscopy, among others. In addition, theoretical studies were conducted to provide greater validity to the experimental results, through calculations based on density functional theory (DFT), Hirshfeld surfaces, and crystal voids. Some additional tools, as the Tanabe-Sugano diagram, electrostatic potential map, crystallinity degree, solubility, and thermal expansion coefficient, were also introduced in the studies to clarify some physicochemical phenomena. It is also important to highlight that experiments based on temperature high conditions were performed using XRD and Raman spectroscopy, in which it was possible to identify and determine new crystalline structures associated with transformations and phase transitions processes. In a complementary way, a study involving the incorporation of impurities in a sulfated matrix was designed to verify the distortions caused by external agents. Finally, the obtained data suggest that the grown crystals are promising candidates to be used in the development of optical devices and in thermochemical energy storage systems.